Effect of temperature on the infectivity of COVID-19 - Ujiie, Mugen; Tsuzuki, Shinya; Ohmagari, Norio (International journal of infectious diseases, 2020)
•The relationship between infectivity of COVID-19 and temperature is not clear.•Mean temperature in February 2020 were associated with the cumulative number of COVID-19 case in Japan on March 16, 2020.•Number of inbound visitors from China and old-age dependency rate were also associated with the cumulative number of cases. To evaluate the influence of temperature on the infectivity of COVID-19 in Japan. We evaluated the relationship between the accumulated number of patients per 1,000,000 population and the average temperature in February 2020 in each prefecture by Poisson regression analysis. We introduced the monthly number of inbound visitors from China in January 2020 in each prefecture and old-age dependency ratio as additional explanatory variables in the model. Monthly inbound visitors from China in January 2020, old-age dependency ratio, and mean temperature in February 2020 are associated with the cumulative number of COVID-19 case on March 16, 2020. Our analysis showed a possible association between low temperature and increased risk of COVID-19 infection. Further evaluation would be desirable at a global level.